AN ANALYSIS OF TRANSLATION TECHNIQUES IN BILINGUAL FOLKTALE BOOKS FOR CHILDREN'S EDUCATION - Susi Dinda Saputri; Dyah Nugrahani; Arso Setyaji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzed translation techniques used in 15 Indonesian-English bilingual folktale books for children based on Molina and Albir’s (2002) framework, supported by Nugrahani et al. (2019). A total of 198 data items were identified and categorized. The study employed a qualitative descriptive method with data collected through document analysis and analyzed using the Miles and Huberman interactive model. The findings revealed 13 out of 18 translation techniques, indicating diverse and context-sensitive translation strategies. Established Equivalent was the most dominant technique (30.3%), followed by Borrowing (18.7%), showing a balance between readability and cultural preservation. Other techniques such as Literal Translation, Calque, Amplification, Explicitation, Description, Discursive Creation, and Modulation were also applied with varying frequencies, while Reduction was the least used. The results indicate that translation techniques in bilingual folktales function not only as linguistic strategies but also as pedagogical tools that support children’s English language acquisition and cultural understanding. Linguistically, they facilitate vocabulary learning and structural recognition, while culturally they preserve Indonesian identity and introduce intercultural awareness. However, techniques such as Generalization, Adaptation, and Deletion may reduce cultural specificity and affect learning quality. Overall, the study confirms that translation techniques play a crucial role in bilingual children’s storybooks as both language-learning media and cultural education tools.